Role of Fashion Involvement and Hedonistic Consumption towards Fashion Apparel Industry - Chauhan, Shaifali; Banerjee, Richa; Risal, Nischal (Pravaha, 2020)
Fashion clothes industry is dependent on endless ideas and new opportunities. The apparel industry replicates people’s lifestyles and represents their social and economic status. The study aims on analyzing the impact of fashion involvement and hedonistic consumption tendency on purchase intention towards fashion apparel industry. The sample contained the representation of population from different cities between the age group 18 to 40. The purposive sampling technique, non-probability sampling techniques and 200 respondents had been selected to collect the data. The result specified that the data was highly reliable with the different values as reported by Cronbach’s Alpha test. Factor analysis, ANOVA, and regression analysis had been done to analyze the data. The regression analysis concluded and proved that there was a positive significant impact of fashion involvement and hedonistic consumption tendency on purchase intention.